A Project-Based Collaborative Learning Model in Islamic Religious Education to Strengthen 21st Century Skills of University Students - Warsiyah Warsiyah; Nor Qomalasari (Universitas Islam Sultan Agung, 2025)
The demands of globalization and the Fourth Industrial Revolution require university students to master 21st century skills, including critical thinking, creativity, communication, and collaboration (4C). Islamic Religious Education (IRE) courses hold strategic potential to cultivate these skills when supported by innovative learning models. This study aims to develop and implement a Project-Based Collaborative Learning model in IRE courses to enhance students’ 21st century skills. Employing a modified Borg and Gall research and development design, the study involved five stages: needs analysis, design, development, implementation, and evaluation. The participants were 30 undergraduate students at Sultan Agung Islamic University (UNISSULA). Data were collected through observation sheets, 21st century skills questionnaires, and in-depth interviews. The findings indicate that the developed model effectively improves students’ critical thinking, teamwork collaboration, creative problem-solving, and academic communication. The average score of students’ 21st century skills increased from the “moderate” to the “high” category after the model’s implementation. These results highlight that project-based collaborative learning in IRE courses not only strengthens religious competencies but also plays a significant role in preparing students to face the challenges of the 21st century global context.